Marketing aspects of functional canned food industrial products - Temesi, Ágoston; Szente, Viktória (Marketing & Menedzsment, 2019)
In our research we have surveyed the consumers’ preferences and attitudes toward canned foods as well as expectations of possible new products. Moreover, we have determined the target groups of possible new products with the help of factor- and cluster-analysis. Hungarian consumers have a demand for canned foods with beneficial health effects, that is the reason why we recommend to develop so-called health protective products. We have surveyed the consumers’ acceptance of possible functional ingredients and the importance of their effects on health in order to help the possible innovation of these products. Dur research shows that Hungarian canned food industrial enterprises would be able to step forward to reach a strong position by producing functional canned foods.